2019
DOI: 10.1080/00222933.2019.1609112
|View full text |Cite
|
Sign up to set email alerts
|

Antennae and the role of olfaction and contact stimulation in mate recognition by males of the pollinating fig wasp Ceratosolen gravelyi (Hymenoptera: Agaonidae)

Abstract: Finding a mate is a crucial step in sexual reproduction. The mutualism between figs and their pollinators is exploited by many figwasps that develop within their galls and attain sexual maturity simultaneously. Male pollinators carry the specific burden of detecting and opening mating holes in galls containing conspecific females before mating with them. The mating behaviourand antennal sensilla of male pollinators associated with Ficus semicordata was investigated to understand mate recognition. Male Ceratoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The presence of the male competitor results in antennae–antennae fighting in P. bliteus as found for Ceratosolen gravelyi Grandi (Hymenoptera: Agaonidae) males with violent combat with biting on their mid or hindleg ( Liu et al 2019 ). Cotesia urabae Austin & Allen (Hymenoptera: Braconidae) males try to interrupt mating by pulling the successful male away from the female ( Avila et al 2016 ).…”
Section: Discussionmentioning
confidence: 88%
“…The presence of the male competitor results in antennae–antennae fighting in P. bliteus as found for Ceratosolen gravelyi Grandi (Hymenoptera: Agaonidae) males with violent combat with biting on their mid or hindleg ( Liu et al 2019 ). Cotesia urabae Austin & Allen (Hymenoptera: Braconidae) males try to interrupt mating by pulling the successful male away from the female ( Avila et al 2016 ).…”
Section: Discussionmentioning
confidence: 88%
“…The mating behaviour of G. cantor has been studied in detail, and it has been confirmed that the male reacts to the female with his antennae or tarsi [45][46][47][48][49], and the male dashes to the female and mounts her back (Fig 1A). According to the results of this experiment, tarsi play an important role in the process of sex pheromone recognition [50,51].…”
Section: Plos Onementioning
confidence: 85%
“…[2b,9b] Such lipid rafts in MDR cell membrane are insoluble in commonly used membrane detergents; thus application of the detergents does not improve cellular nanoparticle uptake. [9a,11] Although the biophysical properties of lipid rafts in MDR cell membranes have been investigated, a drug delivery approach to overcoming lipid rafts‐associated MDR is still lacking. Only a limited number of studies have sought to overcome membrane‐rigidity of MDR cancer cells.…”
Section: Introductionmentioning
confidence: 99%